Network technologies for industry - Сіденко, Б. А.; Холявкіна, Т. В. (Problems of Informatization and Control, 2016)
The article provides analysis of the major network technologies characteristics. The technology oflocal network development with further its extension and utilization in industrial complex is selectedand justified